The Relationship between Excessive Worrying and Social Maladjustment among Internally Displaced Students in Bamenda Municipality: Implication for Clinical Counselling - Fokum, Sigala (American Journal of Education and Practice, 2023)
Purpose: The goal of this study was to investigate the relationship between excessive worrying social maladjustment among internally displaced students in Bamenda municipality. Methodology: The study employed a mixed methods correlational survey research design. The target population of the study consisted of 635 internally displaced students. The purposive and the disproportionate stratified sampling techniques was used to select the sample for the study. Quantitative data was collected through a questionnaire while a semi-structured interview guide was used to collect qualitative data from a sample of 160 participants. Questionnaires were completed by 150 internally displaced while 10 other respondents comprising school administrators, Counsellors and teachers were interviewed. Data was analyzed with the aid of the Statistical Package for Social Sciences (SPSS) version 26.0 for Windows. Descriptive statistics such as simple percentages mean scores and standard deviation, and inferential statistics such as the Pearson Product Moment Correlation test were used to analyze quantitative data while qualitative data were analyzed using content analysis with the support of ATLAS.ti software version 8.0. Findings: The findings revealed that excessive worrying (r=.872, df= 148, p=.000, far < 0.05) have a positive correlation with social maladjustment among internally displaced students in Bamenda municipality. Recommendations: Based on the findings, it was recommended that school Counsellors, teachers and school administrators in the Bamenda municipality should develop and enhance their knowledge and competencies on mechanisms to detect and systematically manage and rehabilitate internally displaced students suffering from Generalized Anxiety Disorder (GAD) in their schools in order to improve the motivation, attention and performance of the learners.